Abyssocladia oxyasters Ekins & Erpenbeck & Goudie & Hooper 2020, sp. nov. - Ekins, Merrick; Erpenbeck, Dirk; Goudie, Lisa; Hooper, John N. A. (Zenodo, 2020)
Abyssocladia oxyasters sp. nov. Figures 4–6, Table 2 urn:lsid:zoobank.org:act: 7A5F1B7E-12E2-4197-8AC6-1BFEF5847C86 Abyssocladia sp. 1, Ekins, Erpenbeck & Hooper, 2020: Table 1. Material examined : Holotype: SAMA S2590, Nullarbor Canyon, Great Australian Bight, South Australia, OR 26, 35 o 3’2.0” S 130 o 54’16.7” E, 3062.72 m, ROV, Coll. CSIRO on RV Rem Etive , Cruise IN 2017_C01, sample RE2017_C01_OR26A_004_108, 23 March 2017. Paratype: SAMA S2591, Nullarbor Canyon, Great Australian Bight, South Australia, OR 26, 35 o 3’2.0” S 130 o 54’16.7” E, 3062.72 m, ROV, Coll. CSIRO on RV Rem Etive , Cruise IN 2017_C01, sample RE2017_C01_OR26A_004_111, 23 March 2017. Etymology : The species is named after the unique characteristic of possessing oxyasters in the endosome of the body (used as a noun in apposition). Distribution : This species is presently known only from type locality in the Great Australian Bight, from bathyal depths. Description : Growth form : Erect pedunculate sponge with a long thin stem. The body is a plano-convex disc on the upward surface parallel to the substrate, and conical lower surface (Figure 4 A). This disc is encircled by radiating filaments (Figure 4 B). The stem is 140 mm in length and only 0.6 mm in width in the holotype, and 160 mm in length and also 0.6 mm in width in the paratype. In both specimens the sponge body has a diameter of 14 mm, and the lower half of the body is a downwards pointing cone of a height of 6.5 mm. The filaments on the holotype are 12 mm long but only 4.2 mm long on the paratype. The basal holdfast is an enlarged disc 9 mm in diameter. Colour : When collected alive the sponge body is orange with a yellowish stem and colourless filaments. After preservation in ethanol the sponge is a light brown colour. Ectosomal skeleton : The ectosomal skeleton of the sponge body is a thin membranous sheet covered with cleistochelae (Figure 5 A). The ectosomal skeletons of the filaments also include cleistochelae and abundant sigmancistras (Figure 5 D), whilst the ectosome of the stem only shows the remains of the cleistochelae (Figure 5 C). Endosomal skeleton : The endosomal skeleton of the sponge body consists mainly of oxyasters that encrust spermatocyst spheres 300–600 µm in diameter. In the stem and filaments the endosomal skeleton consists of longitudinal bundles of mycalostyles 1, with occasional oxyasters in the subectosome. The basal holdfasts contain oxeote anisostyles 2 which are smaller, thicker with greater curvature than megascleres in the rest of the sponge. Megascleres : Very long slender mycalostyles with long tapering points and bases, thickest in the basal third of the spicule, found in the axis of filaments and stem, size range 1380–3810 x 15–54 µm. Styles found in the basal holdfast are oxeote, asymmetrical, curved, with the basal end more abruptly tapering than the apical end, size range 392–1560 x 20–50 µm. Microscleres : Cleistochelae, palmate with three alae. The frontal alae nearly completely detached from the lateral alae, the latter completely fused to the shaft. The shaft is slightly curved. Size range 62–123 x 17–37 µm. Sigmancistras with slight contortion, size range 21.5–40 x 2–7 µm. Oxyasters with only slight central swelling and short slender rays, size range 74–136 µm in diameter (see Table 2). Molecular data: 28S see Figure 1. Remarks : The only other described pedunculate species of Abyssocladia with a long thin stem are: A. hemiradiata Hestetun, Rapp & Xavier, 2017, A. huitzilopochtli Vacelet, 2006 and A. dominalba Vacelet, 2006. There are also the tiny pedunculate species A. bruuni Lévi, 1964 and A. oxeata Koltun, 1970, which all differ from the current species. The cleistochelae of Abyssocladia oxyasters sp. nov. closely resemble those of A. hemiradiata , however, the new species has a very different gross morphology (pedunculate versus stipitate bottle-brush in shape), much larger cleistochelae (62–123 vs. 20–57 µm respectively), and lacks the tylostyles and the large sigmas of the latter species. The cleistochelae in the new species also bear some resemblance to another pedunculate species, A. dominalba Vacelet, 2006, but the new species lacks abyssochelae and the novel anisochelae, and again has a different morphology. The new species differs from A, bruuni Lévi, 1964, as it has a different type and size of cleistochelae, lacks the polytylote styles and has a different morphology (see also Koltun 1970). The new species differs from the pedunculate A. oxeata Koltun, 1970 in lacking oxeas, the different shape of the cleistochelae and different morphology. It differs from A. claviformis Koltun, 1970 by the lack of tylostyles and different gross morphology. Abyssocladia lakwollii Vacelet & Kelly, 2014 is another pedunculate sponge with similar shaped cleistochelae, but it also has additional isochelae and cleistochelae. The Caribbean species A. polycephalus Hestetun, Pomponi & Rapp, 2016 has a similar assortment of cleistochelae, sigmancistras and mycalostyles, but they are all of a different size, and the Caribbean species also has strongyles and a distinctive multi-headed morphology (see Table 1 in Ekins, Erpenbeck & Hooper 2020). Other authors have previously described large single spheres or growths on the underside of other pedunculated Cladorhizidae or on their filaments, that were determined as being reproductive bodies such as spermatocysts or oocytes, e.g. Cladorhiza kensmithi Lundsten et al ., 2017 and C. pteron (Reiswig & Lee, 2007). In some cases microsclere spicule categories were also found to only occur in reproductively mature specimens, associated with these reproductive bodies (e.g. Asbestopluma hypogea Vacelet & Boury-Esnault, 1996, lacking forceps in immature specimens). The abundant spherical bodies observed in both specimens of the new species described here (see Fig. 6 B–D), are unusual in their size (300–600 μm diameter), compared to those spermatocysts or oocytes described from other species in the literature (between 25–100 μm diameter) and are closer in size to the embryos of Asbestopluma (Helophloeina) formosa Vacelet, 2006. All were observed to be densely encrusted with oxyasters. It is hypothesised that these spheres are reproductive bodies (embryos, spermatocysts or oocytes), with the oxyasters (otherwise unique to the Cladorhizidae), associated with them—although we have no immature specimens to compare them with. It is also possible that the oxyasters were sequested from other sponges from the Great Australian Bight with oxyasters such as Tethya irisae (Sorokin et al. , 2019). Alternatively, it is also possible these oxyasters are derived from an internally parasitic tetractinellid sponge, despite their huge abundance in both known specimens of A. oxyasters sp. nov. Copepods were abundantly found in the endosome of all of the specimens (Figure 5 B). Perhaps these copepods could be the vectors or hosts of the parasitising sponge. : Published as part of Ekins, Merrick, Erpenbeck, Dirk, Goudie, Lisa & Hooper, John N. A., 2020, New carnivorous sponges and allied species from the Great Australian Bight, pp. 240-266 in Zootaxa 4878 (2) on pages 247-250, DOI: 10.11646/zootaxa.4878.2.2, http://zenodo.org/record/4424977 : {"references": ["Ekins, M., Erpenbeck, D. & Hooper, J. N. A. (2020) Carnivorous sponges from the Australian Bathyal and Abyssal zones collected during the RV Investigator 2017 Expedition. Zootaxa, 4774 (1), 1 - 159. https: // doi. org / 10.11646 / zootaxa. 4774.1.1", "Hestetun, J. T., Rapp, H. T. & Xavier, J. (2017) Carnivorous sponges (Porifera, Cladorhizidae) from the Southwest Indian Ocean Ridge seamounts. Deep Sea Research Part II: Topical Studies in Oceanography, 137, 166 - 189. https: // doi. org / 10.1093 / zoolinnean / zlw 022", "Vacelet, J. (2006) New carnivorous sponges (Porifera, Poecilosclerida) collected from manned submersibles in the deep Pacific. Zoological Journal of the Linnaean Society, 148, 553 - 584. https: // doi. org / 10.1111 / j. 1096 - 3642.2006.00234. x", "Levi, C. (1964) Spongiaires des zones bathyale, abyssale et hadale. Galathea Report. Scientific Results of The Danish Deep-Sea Expedition Round the World, 1950 - 52, 7, 63 - 112.", "Koltun, V. M. (1970) Sponge fauna of the northwestern Pacific from the shallows to the hadal depths. In: Bogorov, V. G. (Ed.), Fauna of the Kurile-Kamchatka Trench and its environment. Institute of Oceanology of the Academy of Sciences of the U. S. S. R. Vol. 86. Akademiya Nauk SSSR. Trudy Instituta Okeanologii in P. P. Shishov and Izdatelstvo Nauka, Moskwa, pp. 165 - 221.", "Vacelet, J. & Kelly, M. (2014) A new species of Abyssocladia (Porifera, Demospongiae, Poecilosclerida, Cladorhizidae) and other carnivorous sponges from the far eastern Solomon Islands. Zootaxa, 3815 (3), 386 - 96. https: // doi. org / 10.11646 / zootaxa. 3815.3.4", "Hestetun, J. T., Pomponi, S. A. & Rapp, H. T. (2016) The cladorhizid fauna (Porifera, Poecilosclerida) of the Caribbean and adjacent waters. Zootaxa, 4175 (6), 521 - 538. https: // doi. org / 10.11646 / zootaxa. 4175.6.2", "Lundsten, L., Reiswig, H. M. & Austin, W. C. (2017) Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. Zootaxa, 4317 (2), 247 - 260. https: // doi. org / 10.11646 / zootaxa. 4317.2.3", "Reiswig, H. M. & Lee, W. L. (2007) A new species of Cladorhiza (Porifera: Cladorhizidae) from S. California (USA). In: Custodio, M. R., Lobo-Hajdu, G., Hajdu, E. & Muricy, G. (Eds.), Porifera Research. Biodiversity, Innovation and Sustainability. Livros de Museu Nacional 28. Museu Nacional, Rio de Janeiro, pp. 517 - 523.", "Vacelet, J. & Boury-Esnault, N. (1996) A new species of carnivorous sponge (Demospongiae: Cladorhizidae) from a Mediterranean cave. In: Willenz, Ph. (Ed.), Recent Advances in Sponge Biodiversity Inventory and Documentation. Bulletin de l'Institut royal des Sciences naturelles de Belgique, Biologie, 66 (Supplement), pp. 109 - 115.", "Sorokin, S. J., Ekins, M. G., Yang, Q. & Cardenas, P. (2019) A new deep-water Tethya (Porifera, Tethyida, Tethyidae) from the Great Australian Bight and an updated Tethyida phylogeny. European Journal of Taxonomy, 529, 1 - 26. https: // doi. org / 10.5852 / ejt. 2019.529"]}